Village Chiefs and Clientelism: A Reflection After 25 Years of Reform in Indonesia - Agustino, Leo; Hikmawan, M. Dian; Silas, Jonah (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2022)
The village chiefs in the Reform era in Indonesia were expected to transform from being servants of the state to being servants of their community. This hope was accompanied by a lot of support for regulatory changes to create economic equality for most local areas. However, 25 years after the Reform, the village chiefs still exercised great power so that they could easily influence and control the political participation of their citizens. Moreover, the village heads in the Reform era still came from the families of former or incumbent village heads who won the Pilkades because the wealth and connections that had been built for a long time with the villagers became the determinants of the victory of the old families. This article explains the efforts of village heads to maintain their influence so that they continue to be elected in every village head election because the power relations possessed by the old elites are still very influential for exchanging benefits as providers of life and as electoral assets. The art required data were collected in three selected villages such as Sagaherang Kidul Village, Sagalaherang Kaler Village, and Dayeuhkolot Village in Subang Regency, West Java, using a qualitative approach with descriptive method.